The Effect of Inflation, Exchange Rate and Equity Ratio on The Profitability of Indonesian Sharia Bank 2020 - 2024 - Siti, Izzah Afkarina (IJBAMS: International Journal of Business Accounting Management Social Science, 2025)
This study will examine inflation, exchange rates, and equity ratios to assess their impact on the profitability of Bank Syariah Indonesia (BSI) from 2020 to 2024. To ascertain the partial and simultaneous effects of the three factors on profitability, measured by the total profit of the current year, a quantitative approach is employed with multiple linear regression techniques. The findings of the partial test indicate that BSI's profitability was not substantially affected by inflation or exchange rates; however, the equity ratio demonstrated a strong positive influence on the company's profitability. Simultaneously, these three elements significantly influence the level of financial returns generated through profitability. The determination coefficient (R²) of 0.413 indicates that the variables in the model account for 41.3% of the variation in profitability, with other factors contributing to the remaining influence. These data illustrate the significance of equity ratios as indicators of BSI's financial health relative to other macroeconomic factors over the study period